Mitglied fachidiot

fachidiot
Best answer
0
89
Punkte Thumbs up 2

Aktuelle Antworten:

vor 1 Jahr
e^ (-2(a))/e^ (-4(a)) == e^(2a)
Potenzregeln + Erweitern $$ \frac { e^{ -2a } }{ e^{ -4a } } =\frac { e^{ -2a } }{ e^{ -4a } } *\frac { e^{ 4a } }{ e^{ 4a } } =\frac { e^{ -2a+4a } }{ e^{ -4a+4a } }  =\frac { e^{ 2a } }{ e^{0} }  =\frac { e^{ 2a } }{1}   = e^{2a} $$

7-Tage-HistoryAlle Antworten

Für die Hilfe von fachidiot bedanken sich:


André Dalwigk

Reputation Lounge-Netzwerk

Icon mathelounge Mathelounge 89
Icon nanolounge Nanolounge 6

Auszeichnungen

Made by a lovely community
...